A study of the process and patterns that drive florivory across plant lineages and environmental contexts - Maria Gabriela Boaventura de Castro (2023)
This work is the result of a study aimed at evaluating the general patterns and processes that determine the interactions between flowers and florivores. In Chapter I, we summarized the available information to date on florivory through an integrative review that brought together data from published studies up to 2020 and unpublished data collected in the field using a standardized protocol. We compared levels of floral damage between tropical and temperate plants, examined the effects of plant functional traits on floral damage, and explored the eco-evolutionary dynamics of flower-florivore interactions for 180 plant species in 64 families distributed worldwide. Additionally, we identified key research pathways that will help fill persistent knowledge gaps, provided the first global and freely accessible database with information on flower-florivore interactions, and proposed a standardized protocol for measuring florivory. In Chapter II, using flowers from 61 species belonging to 20 families and collected using the a standardized protocol for florivory collect and measurement’s, we assessed the influence of abiotic (environmental) factors and floral traits on florivory levels. The aim of this Chapter II was to examine whether environmental changes caused by urbanization influence florivory levels and whether florivory levels are driven by plant attributes related to urbanization, as well as functional and phylogenetic traits of flowers and species. In this chapter, we provided one of the first assessments of florivory at the species community level through a novel approach, in the context of environmental changes occurring due to urbanization, thus filling an important knowledge gap.